Vertical human-structure interaction of a simply-supported steel-glass composite footbridge under both standing and moving pedestrians. (January 2023) - Wang, Zhihao; Wen, Jinlong; Kou, Chen; Huo, Hongyuan; Chen, Aijiu; Fan, Buqiao
Abstract: For lightweight footbridges, there are evident vertical coupling effects among standing pedestrians, moving pedestrians and the footbridge. To further clarify the vertical human-structure interaction, the effects of a single standing pedestrian, a single moving pedestrian, as well as both a single standing pedestrian and a single moving pedestrian on a simply supported steel-glass composite footbridge model are investigated in this study, respectively. Experimental results show that the effects of standing and moving pedestrians on the structural natural frequencies are different. The Fourier spectrum of the footbridge is sensitive to the relationship between the natural frequency of the coupled system and the walking frequency of the moving pedestrian. Moreover, at the same monitoring point, the vertical velocity of the footbridge is significantly less than that of the centroid of the standing pedestrian. Finally, a corresponding theoretical model is presented in this study. It is found that the theoretical model can well predict vertical dynamic responses of the human-structure coupled system, and the relative relationship of the vertical dynamic response between the footbridge and the standing pedestrian is clarified. This study can provide valuable references for vertical human-structure interaction and vibration serviceability assessment of the footbridge.